2021
DOI: 10.1111/add.15666
|View full text |Cite
|
Sign up to set email alerts
|

Increase in recreational drug use between 2008 and 2018: results from a prospective cohort study among HIV‐negative men who have sex with men

Abstract: Aims To test whether recreational drug use (RDU) and sexualized drug use (SDU) changed in the Amsterdam area between 2008 and 2018 and quantify associations of SDU with condomless anal sex (CAS), recent human immunodeficiency virus (HIV) or sexually transmitted infections (STI) among human immunodeficiency virus (HIV)‐negative men who have sex with men (MSM). Design Open prospective cohort study. Setting Public Health Service of Amsterdam, the Netherlands. Participants A total of 976 HIV‐negative MSM, aged ≥ 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 52 publications
0
25
0
2
Order By: Relevance
“…In the same study, chemsex drug use was associated with the greatest elevations in multiple indicators of HIV risk [ 2 ]. Although some evidence showed the declining use of mephedrone and GHB in the UK [ 7 ], SDU and chemsex drug use increased in a cohort of SMM in Amsterdam, Netherlands, from 2008 to 2018 [ 8 ]. Other recent findings from this Dutch cohort demonstrated that SMM classified as engaging in chemsex drug use had 15-fold greater odds of a sexually transmitted infection (STI) relative to those reporting no substance use [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the same study, chemsex drug use was associated with the greatest elevations in multiple indicators of HIV risk [ 2 ]. Although some evidence showed the declining use of mephedrone and GHB in the UK [ 7 ], SDU and chemsex drug use increased in a cohort of SMM in Amsterdam, Netherlands, from 2008 to 2018 [ 8 ]. Other recent findings from this Dutch cohort demonstrated that SMM classified as engaging in chemsex drug use had 15-fold greater odds of a sexually transmitted infection (STI) relative to those reporting no substance use [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…That said, while a very important factor, sex is only one of the reasons for using drugs, there are many others, and—with the exception of alkyl nitrites and the four chem drugs—psychoactive drugs are probably used more frequently by most MSM for purposes other than sex. In addition, some recent articles suggest that drug use, both for sex and recreational purposes, is increasing, in both HIV-positive [ 15 ] and HIV-negative MSM [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…13 Moreover, a previous analysis within our cohort showed strong associations between specific SDU and CAS, HIV, and STI. 12 This suggests that MSM with these characteristics could be specifically targeted for sexual behavior counseling that targets the prevention and management of STI, including counseling on sexual behavior in the context of SDU.…”
Section: Discussionmentioning
confidence: 99%
“…Specific SDU was defined as the use of mephedrone, methamphetamine, gamma hydroxybutyrate (GHB)/gamma butyrolactone (GBL), ketamine, amphetamine, cocaine, and/or ecstasy (XTC)/methylenedioxy-methylamphetamine (MDMA) during sex. 12 Any STI was defined as having a newly diagnosed chlamydia, gonorrhea, or syphilis, whereas any anal STI was defined as having a newly diagnosed anal chlamydia or anal gonorrhea.…”
Section: Methodsmentioning
confidence: 99%